Zinc Impurity in Drinking Water and Its Toxic Effect on Human Health (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
The levels of zinc (Zn) pollution in several water sources as ground, river, tap, lake water etc. Zinc are possibly toxic and are moved to the nearby environment through different pathways. Among mining activity, waste dump contaminants one of the most hazardous groups for of their determined nature, tendency, toxicity, to collect in creatures and undertake food chain increase and more still, they are non-degradable. Zinc concentration are found in water are higher than the permissible limits of WHO, USEPA that gives an indication of hazardous risk to human health. This review study also reveals that zinc contamination through water and major health effects on human health.
Keywords: Heavy metals; Zinc; Environment; Water; Toxicity